Nanoparticles for the potential treatment of Alzheimer’s disease: A physiopathological approach - Navarro Martínez Nicolás; Toledo Hernández Jorge; Morales Javier O. (Nanotechnology Reviews, 2023)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative central system disease with a high prevalence among the elderly and is the most common form of dementia. Oxidative stress is crucial on AD pathogenesis and leads to deposition of neurofibrillary tangles and Aβ plaques; therefore, the use of natural antioxidants or ROS scavengers could help avoid the formation of these aggregates. Similarly, Aβ-degrading/anti-aggregating molecules could help arrest AD progression. Otherwise, traditional anti-Alzheimer drugs such as acetylcholinesterase inhibitors help improve memory and attention deficits. Nevertheless, all these drugs are extensively metabolized, have low plasma concentration, and cannot cross the blood–brain barrier freely. This review discusses different strategies for nanocarrier conjugation of these drugs for brain targeting and delivery, and new approaches on AD treatment according to the most accepted hypotheses of AD pathogenesis. Although none of the existent compounds or drugs can completely arrest the disease’s progression, nanocarrier development of anti-Alzheimer drugs could help delaying the initial or late stages of neurodegeneration. The discovery of new and more complex nanosystems with multiple approaches in AD treatment is needed and will be the next step in AD treatment in the near future.